The Role of Community Organisation, Religion, Spirituality and Cultural Beliefs on Diabetes Social Support and Self-Management in Sub-Saharan Africa: Integrative Literature Review - Molla, Israel Bekele (Journal of religion and health, 2025)
To examine the evidence for the role of community organisations, religion, spirituality, cultural beliefs, and social support in diabetes self-management, we undertook an integrative literature review utilising MEDLINE, APA PsycINFO, CINAHL, and grey literature databases. The selected articles were appraised for quality, and the extracted data were analysed thematically. The search yielded 1586 articles, and after eliminating duplicates, 1434 titles and abstracts were screened, followed by a full-text review of 103 articles. Ultimately, 47 articles met the inclusion criteria for the review, utilising various study designs, including qualitative, quantitative, mixed-methods, and nonrandomised clinical trials. These findings indicate that spirituality and religiosity can positively affect diabetes self-management by providing motivation, coping skills, social support, and guidance for healthy behaviours. A strong social support system enhances diabetes self-management and glycaemic control for individuals with diabetes. However, some aspects of religion and culture, such as beliefs about medications, may also pose challenges or barriers to diabetes self-management. Adherence to medication, food choices, physical activity, and the use of complementary or alternative medicine can be influenced by sociocultural factors. Additionally, cultural beliefs and social norms influence understanding diabetes aetiology, management, and symptom reactions. The findings highlight that it is crucial to understand the cultural, religious, or spiritual influences that can either assist or impede self-management habits in individuals with diabetes and could inform interventions that support personalised and effective care.